Global Economic Prospects, January 2012 : Uncertainties and Vulnerabilities - World Bank (Washington, DC, 2013)
The world economy has entered a dangerous period. Some of the financial turmoil in Europe has spread to developing and other high-income countries, which until earlier had been unaffected. This contagion has pushed up borrowing costs in many parts of the world, and pushed down stock markets, while capital flows to developing countries have fallen sharply. Europe appears to have entered recession. At the same time, growth in several major developing countries (Brazil, India and, to a lesser extent, Russia, South Africa and Turkey) is significantly slower than it was earlier in the recovery, mainly reflecting policy tightening initiated in late 2010 and early 2011 in order to combat rising inflationary pressures. As a result, and despite a strengthening of activity in the United States and Japan, global growth and world trade have slowed sharply.